An optimal protocol for dynamic stretching to improve explosive performance - Yamaguchi, T.; Ishii, K. (The Journal of Physical Fitness and Sports Medicine, 2014)
Previous studies have indicated that dynamic stretching acutely improves explosive performance, and dynamic stretching is now incorporated into warm-up protocols prior to sports activities that require explosive performance. The optimal protocol for dynamic stretching, however, has not been clarified. The purpose of this review is to clarify the optimal protocols for velocity and volume (i.e., repetition or distance x set) in dynamic stretching to improve explosive performance by systematic investigation. For velocity, the rate of change in explosive performance when dynamic stretching was performed "as fast as possible" (7.6 ± 3.8%) was significantly (P < 0.01) greater compared to when dynamic stretching was performed "without setting the velocity" (1.1 ± 5.3%). This finding suggested that dynamic stretching should be performed "as fast as possible". As for volume, the repetition of dynamic stretching was significantly (P < 0.01) negatively correlated with the rate of change in explosive performance only when dynamic stretching was performed without setting the velocity. The distance of dynamic stretching was also significantly (P < 0.05) negatively correlated with the rate of change in explosive performance. These findings suggest that explosive performance might become impaired as the volume of dynamic stretching increases. By combining simple regression analysis of the repetition or the distance of dynamic stretching and the rate of change in explosive performance with a systematic investigation, it was found that the optimal "repetition" or "distance" x "set" of dynamic stretching was "10-15 repetitions" or "10 yards-20 meters" x "1-2 sets", respectively.